A review of technology and policy deep decarbonization pathway options for making energy-intensive industry production consistent with the Paris Agreement. (20th June 2018) - Bataille, Chris; Åhman, Max; Neuhoff, Karsten; Nilsson, Lars J.; Fischedick, Manfred; Lechtenböhmer, Stefan; Solano-Rodriquez, Baltazar; Denis-Ryan, Amandine; Stiebert, Seton; Waisman, Henri; Sartor, Oliver; Rahbar, Shahrzad
Abstract: The production of commodities by energy-intensive industry is responsible for 1/3 of annual global greenhouse gas (GHG) emissions. The climate goal of the Paris Agreement, to hold the increase in the global average temperature to well below 2 °C above pre-industrial levels while pursuing efforts to limit the temperature increase to 1.5 °C, requires global GHG emissions reach net-zero and probably negative by 2055–2080. Given the average economic lifetime of industrial facilities is 20 years or more, this indicates all new investment must be net-zero emitting by 2035–2060 or be compensated by negative emissions to guarantee GHG-neutrality. We argue, based on a sample portfolio of emerging and near-commercial technologies for each sector (largely based on zero carbon electricity & heat sources, biomass and carbon capture, and catalogued in an accompanying database), that reducing energy-intensive industrial GHG emissions to Paris Agreement compatible levels may not only be technically possible, but can be achieved with sufficient prioritization and policy effort. We then review policy options to drive innovation and investment in these technologies. From this we synthesize a preliminary integrated strategy for a managed transition with minimum stranded assets, unemployment, and social trauma that recognizes the competitive and globally traded nature of commodity production. The strategy includes: an initial policy commitment followed by a national and sectoral stakeholder driven pathway process to build commitment and identify opportunities based on local zero carbon resources; penetration of near-commercial technologies through increasing valuation of GHG material intensity through GHG pricing or tradable performance based regulations with protection for competitiveness and against carbon leakage; research and demand support for the output of pilot plants, including some combination of guaranteed above-market prices that decline with output and an increasing requirement for low carbon inputs in government procurement; and finally, key supporting institutions. Graphical abstract: Image 1 Highlights: Global climate goals require industry be zero or negative GHG emitting by 2055-'80. Industry is hard to decarbonize due to cost, trade sensitivity, and long facility life. Immature technologies exist to decarbonize all industrial commodity production. Knowledge of industry mitigation options is low, leading to skewed policy & effort. Policies combining R&D, commercialization support and GHG pricing are needed.